HYBRID ACTIONS IN ELECTORAL POLITICAL PROCESSES (Heritage, 2023)
Hybrid actions in electoral political processes are an increasingly prevalent phenomenon in the modern structure of political relations and today's electoral engineering. Regardless of the present controversy regarding the personification of hybrid action, the scope and effects of such activities do not necessarily have to be destructive. This stems from the fact that, thanks to hybrid actions, political changes have been achieved in some countries that have brought with them to these societies’ prosperity and wealth. Although this is difficult to assess nowadays, given the enormous intertwining of different vectors of domestic and foreign policies, and beyond that interests, which is especially evident in the era in which we live, in the era of deforestation of public international law and the modern world order. The paper analyzes all the most important aspects of hybrid actions within the electoral political processes, but with efforts to, through a careful and balanced research approach, theoretically shed light on the true essence and background of hybrid action on the gender process of government - on political elections.
Keywords: Hybrid actions, political elections, government, political parties, special services, media